Influence of some in situ environmental factors on growth performances of Calamus caesius - Bonal, D. (2018)
Growth performances of 480 Calamus caesius seedlings distributed in 16 experimental plots in Luasong Forestry Centre, Sabah, Malaysia, were assessed yearly since establishment. At three years after planting, noticeable differences of mean annual increment of the length per stem and the number of stems per plant were found and a factor analysis was conducted to study the effect of five in situ environmental factors (canopy conditions, percentage of opened canopy, support tree density, topography, slope) on the growth parameters. An increase in the amount of light reaching the plants resulting from openings in the canopy strongly favoured the development of new stems but not the stem length increment. The latter parameter appeared to be positively correlated to the age of seedlings at planting.